ANKLE ARTHROSCOPIC SURGERY FOR THE TREATMENT OF SYNOVIAL CHONDROMATOSIS. A CASE REPORT (Vietnam Journal of Community Medicine, 2022)
Synovial chondromatosis of the joints is a rare benign disease of unknown etiology. The disease can arise in the synovial membrane of joints or tendon sheaths. Synovial chondromatosis is characterized by multiple loose bodies in the joint, they cause symptoms such as swelling, pain and limitation of joint movement, which can lead to structural damage in the long term. We describe the case of a 42-year-old male patient who was diagnosed with a right ankle synovial chondromatosis. X-ray and MRI images showed two synovial chondromatosis that located in the anterior and posterior compartments of the subtalar joint. The patient was successfully treated by arthroscopic removal of loose bodies in the joint and partial synovial resection.Clinical follow-up after one month and two months and 24 months, ankle joint function was completely normal. MRI 24 months after surgery showed showed no sign of tumor recurrence. Conclusion: Arthroscopy of the ankle joint is an effective, safe, and minimally invasive treatment method. When diagnosing synovial chondromatosis in the ankle joint, surgery should be done early to prevent secondary joint damage.
Keywords: Synovial chondromatosis, loose bodies, arthroscopy.